Development of evaluation index system for functional ability of older patients with stroke based on healthy aging: a modified Delphi study - Zhang, Wei; Tao, Xiu-bin; Fan, Xiao-li; Wang, Ai-ping (Frontiers in Public Health, 2025)
BackgroundThe prevalence of stroke in the older population is high and it is critical to promote and maintain the functional status of older patients post stroke. Health measures centered on functional ability can scientifically reflect the health status of older individuals. The aim of this study was to develop an evaluation index system for assessing the functional ability of older patients with stroke based on the World Health Organization Healthy Aging Model.MethodsKey indicators were identified through literature analysis and semi-structured interviews with 10 older patients with stroke. A two-round expert consultation process was conducted to evaluate and revise the indicators. Subsequently, a hierarchical construction model was established using the analytic hierarchy process to determine the weight of each level indicator.ResultsThe evaluation index system comprised three first-level, 13 s-level, and 53 third-level indicators. The weights ranged from 0.143–0.429 for first-level indicators, 0.052–0.349 for second-level indicators, and 0.040–0.667 for third-level indicators.ConclusionThe developed evaluation index system demonstrates reliability for assessing the functional ability of older stroke patients and provides a standardized framework for nursing staff to conduct functional assessment of older stroke patients.